A reassessment of the use of unit labor costs as a tool for competitiveness and policy analyses in India - Jesus Felipe; Utsav Kumar (Levy Economics Institute of Bard College, 2010)
We reinterpret unit labor costs (ULC) as the product of the labor share in value added, times a price adjustment factor. This allows us to discuss the functional distribution of income. We use data from India's organized manufacturing sector and show that while India's ULC displays a clear upward trend since 1980 (with a decline since the early 2000s), this is exclusively the result of the increase in the price deflator used to calculate the ULC. The labor share of India's organized manufacturing sector has been on a downward trend, from 60 percent in 1980 to 26 percent in 2007. This means that the sector's capital share increased from 40 to 74 percent over the same period. We also find that real wages have increased minimally during the period analyzed-well below labor productivity-while the real profit rate and unit capital costs have increased substantially. We conclude that if India's organized manufacturing sector has lost any competitiveness, it is the result of the increase in unit capital costs. Our analysis questions policy recommendations that advocate wage moderation, which result from simply looking at the evolution of the ULC, and that blame the loss of competitiveness on high or increasing wages.
Keywords: D31; D33; E25; J30; O47; 330; capital productivity; capital share; competitiveness; functional distribution of income; India; labor productivity; labor share; real rate of profit; real wage rate; unit capital cost; unit labor cost